DETECT Schools Study Protocol: A Prospective Observational Cohort Surveillance Study Investigating the Impact of COVID-19 in Western Australian Schools - Mullane, Marianne J.; Thomas, Hannah M.; Epstein, Melanie; Mandzufas, Joelie; Mullan, Narelle; Whelan, Alexandra; Lombardi, Karen; Barrow, Tina; Ang, Sherlynn; Leahy, Adele; Cameron, Ewan; Lester, Leanne; et al. (Frontiers in Public Health, 2021)
Introduction Amidst the evolving COVID-19 pandemic, understanding the transmission dynamics of the SARS-CoV-2 virus is key to providing peace of mind for the community and informing policy-making decisions. While available data suggest that school-aged children are not significant spreaders of SARS-CoV-2, the possibility of transmission in schools remains an ongoing concern, especially among an aging teaching workforce. Even in low-prevalence settings, communities must balance the potential risk of transmission with the need for students’ ongoing education. Through the roll out of high-throughput school-based SARS-CoV-2 testing, enhanced follow-up for individuals exposed to COVID-19 and wellbeing surveys, this study investigates the dynamics of SARS-CoV-2 transmission and the current psycho-social wellbeing impacts of the pandemic in school communities. Methods The DETECT Schools Study is a prospective observational cohort surveillance study in 79 schools across Western Australia (WA), Australia. To investigate the incidence, transmission and impact of SARS-CoV-2 in schools, the study comprises three ‘modules’: Module 1) Asymptomatic spot-testing in schools to screen for asymptomatic SARS-CoV-2; Module 2) Enhanced surveillance of close contacts following the identification of any COVID-19 case to determine the secondary attack rate of SARS-CoV-2 in a school setting; and Module 3) Survey monitoring of school staff, students and their parents to assess psycho-social wellbeing following the first wave of the COVID-19 pandemic in WA. Ethics and dissemination This study was approved by health ethics review committees at the Child and Adolescent Health Service (PRN RGS0000004059) and the WA Aboriginal Health Ethics Committee (PRN 993), and is conducted in partnership with the WA Departments of Health and Education. Study findings will be shared with stakeholders through regular reporting, and with the academic, medical, and broader communities through scientific publications, presentations, and media releases. Testing numbers and results will be shared iteratively with the public through social media. Trial registration number ACTRN12620000922976